Hubungan Penggunaan Gadget Dengan Motivasi Dan Prestasi Belajar Siswa Kelas IX DI SMP Swasta Ira Medan - Zebua, Ester Tri Afida; Tambunan, Dior Manta (Universitas Murni Teguh, 2025)
The use of Gadgets around the world continues to increase from year to year. But in reality,very few teenagers or junior high school students use Gadgets properly. They tend to use theseGadgets for things they don't need at their age. Excessive use of Gadgets can result indecreased learning motivation, impaired concentration, and laziness in learning. As a result,students are always obsessed with using Gadgets and forget their learning commitments whichhave an impact on their achievements. The purpose of this study was to determine theRelationship between Gadget Use and Motivation and Learning Achievement of Grade IXStudents at IRA Medan Private Junior High School. The research method used a quantitativeresearch type with an analytical survey method with a research design in the form of DescriptiveCorrelation with a Cross-Sectional approach. The number of samples in this study was 53students. The sampling technique in this study was Total sampling. The bivariate test used toanalyze the data in this study was the Spearman non-parametric test because the data wasnot normally distributed according to the results of the Kolmogorov Smirnov test. The results ofthe study showed that there was a relationship between the use of gadgets and motivation witha p-value = 0.004 (α <0.05) and there was no relationship between the use of gadgets andlearning achievement with a p-value = 0.491 (α > 0.05). It can be concluded that there is arelationship between the use of gadgets and the motivation of grade IX students at IRA MedanPrivate Junior High School and there is no relationship between the use of gadgets and thelearning achievement of grade IX students at IRA Medan Private Junior High School. It isrecommended to conduct further research with more samples and add the variables Stress,Mental Health, Eye Health, and Early Adolescents as respondents.